Gray water dominance in water footprint assessment of shale oil: A lifecycle perspective - Qian Wang; Bo Yuan; Jian Wu; Jun Xiong; Wenshi Liu; Xi Chen; Yan Wu (Energy Nexus)
Shale oil has emerged as a significant issue in global energy reform and sustainable development, recognized for its high water consumption. Existing water footprint studies, which predominantly focus on shale gas, inadequately address shale oil's unique resource characteristics and neglect key factors such as wastewater treatment. This study developed a Water Footprint Assessment Tool (WFAT) that integrates regression-based empirical models derived from historical shale oilfield data with the Water Footprint Network (WFN) methodology, aiming to holistically evaluate the water footprint across the entire shale oil production lifecycle. The WFAT systematically quantifies blue water footprint and incorporates the gray water footprint linked to wastewater treatment demands and energy-related indirect water footprint. When applied to a shale oilfield in Qingyang city, the WFAT results indicate a total water footprint of 107.39 m³/t, primarily driven by hydraulic fracturing process. Notably, the blue water footprint contributes merely 1.52% to the total footprint, while the gray water footprint dominates (98.15%), with fracturing-induced flowback water treatment being the largest contributor. Shale oil exhibits higher water use intensity (26.12 L/GJ) compared to shale gas (2.6 to 9.3 L/GJ) but aligns with coal and natural gas, and its produced water intensity (25.5 L/GJ) surpasses shale gas (3.9–7.3 L/GJ), reflecting greater water production attributed to geological-engineering synergies. The recycling rate of flowback water is identified as a pivotal parameter for footprint reduction through sensitivity analysis. This study provides a reference for water resource assessment and management to balance energy extraction with water conservation in water-stressed regions.